2016
DOI: 10.1373/clinchem.2016.258236
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Base-Position Error Rate of Next-Generation Sequencing to Detect Tumor Mutations in Circulating DNA

Abstract: Targeted next-generation sequencing analyzed with the base-PER method represents a robust and low cost method to detect circulating tumor DNA in patients with cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 41 publications
1
52
0
1
Order By: Relevance
“…A previous assessment of NGS performance in clinical samples showed a high level of agreement with dPCR for EGFR and KRAS mutations [27]. In the present study, double testing of 59 patients with EGFR -, KRAS -, or BRAF -mutated tumors confirmed these results (Fig 2).…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…A previous assessment of NGS performance in clinical samples showed a high level of agreement with dPCR for EGFR and KRAS mutations [27]. In the present study, double testing of 59 patients with EGFR -, KRAS -, or BRAF -mutated tumors confirmed these results (Fig 2).…”
Section: Resultssupporting
confidence: 88%
“…Droplets were loaded into the RainDrop Sense instrument and analyzed using RainDrop Analyst software. To calculate the percentage of mutations, a limit of blank was determined for each assay [29] and applied to all samples as previously described [27]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another approach was to improve alteration detections using adapted statistical methods. Thus, determination of the base position-error rate (BPER) from control samples allowed detection of true mutations as low as 0.003% and 0.001% for indels after statistical computational [44]. …”
Section: Technical Approaches For Ctdna Detection and Analysismentioning
confidence: 99%